2007
DOI: 10.1523/jneurosci.2110-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

From Numerosity to Ordinal Rank: A Gain-Field Model of Serial Order Representation in Cortical Working Memory

Abstract: Encoding the serial order of events is an essential function of working memory, but one whose neural basis is not yet well understood. In the present work, we advance a new model of how serial order is represented in working memory. Our approach is predicated on three key findings from neurophysiological research: (1) prefrontal neurons that code conjunctively for item and order, (2) parietal neurons that represent count information through a graded and compressive code, and (3) multiplicative gain modulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(131 citation statements)
references
References 54 publications
7
122
1
1
Order By: Relevance
“…Moreover, in tasks such as the ones used here, behavioral evidence strongly supports the idea that subjects do not proceed from action to action by a chain of reflexes but instead maintain an incrementally updated internal representation of ordinal position and select at each stage the action associated with the current representation (Orlov et al 2002). Several successful computational models exploit explicit representations of either absolute ordinal position (Beiser and Houk 1998;Botvinick and Watanabe 2007;Dominey et al 1998a;Fukai 1999;Orlov et al 2002;Salinas 2009) or ordinal position as defined relative to the beginning and end of a sequence (Henson 1998;Rosenbaum et al 2007). Our findings are compatible with these ideas in that they demonstrate the presence in frontal cortex of ordinal position signals independent of signals reflecting extraneous factors commonly correlated with rank (Fig.…”
Section: Functional Significancesupporting
confidence: 61%
“…Moreover, in tasks such as the ones used here, behavioral evidence strongly supports the idea that subjects do not proceed from action to action by a chain of reflexes but instead maintain an incrementally updated internal representation of ordinal position and select at each stage the action associated with the current representation (Orlov et al 2002). Several successful computational models exploit explicit representations of either absolute ordinal position (Beiser and Houk 1998;Botvinick and Watanabe 2007;Dominey et al 1998a;Fukai 1999;Orlov et al 2002;Salinas 2009) or ordinal position as defined relative to the beginning and end of a sequence (Henson 1998;Rosenbaum et al 2007). Our findings are compatible with these ideas in that they demonstrate the presence in frontal cortex of ordinal position signals independent of signals reflecting extraneous factors commonly correlated with rank (Fig.…”
Section: Functional Significancesupporting
confidence: 61%
“…In an early study of Scottish low birth-weight children, Drillien and colleagues (1980) reported that the combination of low socioeconomic status and preterm birth has a dramatic negative impact on intellectual performance (Botvinick & Watanabe, 2007). Our studies so far have not addressed whether this is also the case in a Swedish population of children born preterm in the early 1990s, where there has been universal access to maternal health and perinatal care of high quality.…”
Section: Parental Educationmentioning
confidence: 88%
“…Item retention abilities were minimized because item information was fully provided at recall and only the serial order of the items within the target sequence needed to be reconstructed. The precision of serial order coding was estimated by determining the number of positions each erroneously reconstructed item had migrated and by comparing the number of large migrations (three, four, or five positions) relative to the number of small migrations (one or two positions) (Estes, 1972;Lee & Estes, 1981); the index was computed in such a way (see Method for details) that a higher value of the index reflected a higher precision of serial coding by assuming that precise serial order representations lead to small distance migrations and broad representations lead to large distance migrations, based on a number of experimental studies showing that the vast majority of migration errors in immediate serial reproduction tasks are one or two position migrations (e.g., Botvinick & Watanabe, 2007;Burgess & Hitch, 1999;Henson, 1998). Item STM was assessed via a single nonword delayed repetition task maximizing retention of item information by requiring children to process, store, and repeat short unfamiliar phonological patterns with minimal opportunity for the occurrence of serial order errors (Leclercq & Majerus, 2010).…”
Section: The Current Studymentioning
confidence: 99%